141 Increased incidence of cervical adenosquamous cell carcinoma in minority populations. (13th November 2020) - Liao, C; Furey, K; Richardson, M; Tran, K; Tian, C; Darcy, KM; Kapp, DS; Cohen, JG; Chan, JK
Abstract : Objective: To observe trends in the incidence of Adenosquamous Cell Carcinoma of the cervix (ASC) in regards to race and age. Methods: From 2001 to 2016, incidence rates of cervical cancer were estimated from United States Cancer Statistics. SEER*Stat and Joinpoint regression were used to calculate the incidence rate (per 100, 000) and average annual percent change (AAPC), adjusted for hysterectomy and pregnancy prevalence data from the Behavioral Risk Factor Surveillance System. Results: Adenosquamous cell carcinoma accounted for 6, 599 of 200, 000 (3.3%) cases of cervical cancer from 2001–2016; of which 4, 165 were White (63.1%), 830 were Black (12.6%), 1, 155 were Hispanic (17.5%), 345 were Asian (5.2%) and 104 were unidentified (1.6%). There was a 3.9% decrease in incidence per year; from 0.47/100, 000 in 2001 to 0.24/100, 000 in 2016 after adjusting for age and race (p<0.001). The incidence of ASC is nearly 1.5-fold greater for Hispanics at 0.38 per 100, 000 compared to Whites (0.25) and Blacks (0.27). Additionally, the Hispanics had a bimodal age distribution at diagnosis, with peaks at 40–44yo and 65–69yo (0.76 and 0.69) compared to Whites with a single peak diagnosis at 40–44yo (0.56/100, 000). Conclusion: Hispanics have a 50% higher incidence of adenosquamous cell cervical carcinoma compared to others. Their incidence peaks in the early 40's and late 60's year olds. The difference in incidence and age distribution of this cancer warrant further investigation.